Implementasi QR Untuk Legalitas Tanda Tangan Digital di Lingkungan STMIK Bandung - Indra Maulana Yusup Kusumah; Efrizal Fikri Yusmanyah; Meidi Fransisca Siregar; Puput Fatmawati (LPPM STMIK Bandung, 2024)
The use of electronic documents and academic letters raises problems regarding the validity of digital signatures and document security. This research introduces a solution by applying QR Code technology for the legality of digital signatures in the STMIK Bandung environment. Problems identified include the absence of a digital signature verification system, a manual signing process, and the risk of signatures being duplicated and manipulated. This research focuses on designing and implementing a signature verification system using QR Code technology. The main goal is to create a system that can verify the authenticity of signatures on documents and letters using QR Codes. This system provides a unique QR Code for each person and document, minimizing the risk of signatures being copied and duplicated. The result of this research is the implementation of a digital signature verification system using QR Code which can increase security, efficiency, accuracy and productivity in managing academic documents and letters at STMIK Bandung.